Моделювання імовірності відмови автоматичного газового захисту шахти - Ilchuk, Volodymyr; Hlushchuk, Vladyslav (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
Розроблено імовірнісну математичну модель, з використанням логіко-імовірнісного методу та дерева відмов, автоматичного газового захисту шахти, що дозволяє оцінити імовірність виникнення події «вибух» в гірничій виробці. Необхідність удосконалення захисту при стаціонарних і нестаціонарних процесах метаноутворення підтверджується перевищенням фактичної імовірності вибуху нормованого значення на два порядки. A probabilistic mathematical model has been developed, using the logical-probabilistic method and a fault tree, of automatic mine gas protection, which allows estimating the probability of an "explosion" event in a mine. The need to improve protection during stationary and non-stationary processes of methane formation is confirmed by the fact that the actual probability of an explosion exceeds the normalized value by two orders of magnitude.